FORMULATION AND OPTIMIZATION OF GUGGUL LIPID PHYTOSOMAL GEL OF THYMOQUINONE USING 22 FACTORIAL DESIGN (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Thymoquinone is a bioactive principal constituent of Nigella Sativa. Thymoquinone is hydrophobic, having low water solubility and less permeability. The study aimed to formulate and optimize Thymoquinone loaded phytosomes using guggul lipid by thin-film method to enhance permeation and stability. 2 factor 2 level design (22) using SigmaTech software was employed contour plots were used to predict the responses. The two independent variables used were: the amount of guggul lipid (X1), amount of cholesterol (X2); and the responses included entrapment efficiency (Y1), in-vitro drug release (Y2), and particle size (Y3). The optimized formulation of Thymoquinone phytosomes was incorporated into Carbopol 934 gel base and 0.4% thymoquinone phytosomal gel was prepared. The phytosomal gel was evaluated. The stability study was performed, and phytosomal gel formulation was found stable at 4°C for 45 days.